Classification of Lubricant Oil Adulteration Level using Case-Based Reasoning - Suhaimi, Mohd Daud; M. S., Najib; Nurdiyana, Zahed; Mohd Falfazli, Mat Jusof; Muhammad Firdaus, Che Jusoh@Yusoff; Muhammad Izzat Izzuddin Nai’mullah, Hassim (The Society for Advancement of Science & Technology, 2017)
The main purpose of this paper is to classify lubricant oil odor-profile using Case-based Reasoning classifier. Electronic nose was used for the purpose of taking data readings for each lubricant oil smell sample. The data that have been collected will be normalized so that the data can be evaluated in a smaller scale to establish an odor-profile for each sample. Then the odor-profiles were classified using Case-based Reasoning (CBR) classifier. The classification performance resulting 100% successfully correct classification.